A low-noise programmable gain amplifier with fully balanced differential difference amplifier and class-AB output stage. (June 2017) - Wang, Jingyu; Zhu, Zhangming; Liu, Shubin; Ding, Ruixue
Abstract: A programmable gain amplifier (PGA) is presented, targeting amplifying input signal with high dynamic range and low noise. The proposed PGA adopts fully balanced differential difference amplifier (FBDDA) as main amplifier. A class-AB implementation of output stage is advantageous in order to achieve high current driving capability with very low quiescent power consumption. Combining resistor-feedback loop controlled by digital signal, the proposed PGA achieves a dB-linear gain range from 0 to 15 dB with a gain step of 1 dB. Compared with previous works, the theoretical analysis and measurement results prove that the proposed structure has lower noise. The circuit was designed and fabricated in SMIC 0.18 µm 3.3 V process, showing a gain error of less than 0.25 dB, a third harmonic distortion (HD3) of better than −83 dB and a thermal noise of 1.6 nv / Hz . The measurement results indicate that the PGA described here has a −3 dB bandwidth of 387.5 MHz at maximum gain of 15 dB. The PGA occupies a chip area of 0.1 mm 2 .